2013
DOI: 10.1101/gad.186916.112
|View full text |Cite
|
Sign up to set email alerts
|

Ing1 functions in DNA demethylation by directing Gadd45a to H3K4me3

Abstract: Active DNA demethylation regulates epigenetic gene activation in numerous processes, but how the target site specificity of DNA demethylation is determined and what factors are involved are still poorly understood. Here we show that the tumor suppressor inhibitor of growth protein 1 (Ing1) is required for targeting active DNA demethylation. Ing1 functions by recruiting the regulator of DNA demethylation growth arrest and DNA damage protein 45a (Gadd45a) to histone H3 trimethylated at Lys 4 (H3K4me3). We show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 75 publications
4
38
0
1
Order By: Relevance
“…GADD45 proteins participate in repair-based DNA demethylation by recruiting the base-excision or the nucleotide-excision repair machinery (BER and NER, respectively; Jung et al, 2007; Schäfer, 2013). Interestingly, it has been reported that Gadd45 gene expression can be induced by cellular stress (Hollander and Fornace, 2002), ultimately initiating GADD45-mediated DNA demethylation which, notably, seems to be restricted to single genes (Schmitz et al, 2009; Gavin et al, 2012; Schäfer et al, 2013), without affecting global DNA demethylation (Engel et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…GADD45 proteins participate in repair-based DNA demethylation by recruiting the base-excision or the nucleotide-excision repair machinery (BER and NER, respectively; Jung et al, 2007; Schäfer, 2013). Interestingly, it has been reported that Gadd45 gene expression can be induced by cellular stress (Hollander and Fornace, 2002), ultimately initiating GADD45-mediated DNA demethylation which, notably, seems to be restricted to single genes (Schmitz et al, 2009; Gavin et al, 2012; Schäfer et al, 2013), without affecting global DNA demethylation (Engel et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Gadd45a mediates nucleotide exchange DNA repair and thus demethylation (Barreto et al, 2007; Ma, Guo, Ming, & Song, 2009; Niehrs & Schafer, 2012). However, Gadd45a protein lacks a DNA binding domain and depends on tumor suppressor inhibitor of growth protein 1 (ING1) to recruit to promoters enriched with H3K4me3, which then triggers locus specific DNA demethylation (Schafer, Karaulanov, Stapf, Doderlein, & Niehrs, 2013). In short, epigenetic modifications include histone methylations, DNA methylation and demethylation, which coordinate to regulate lineage-specific gene expression.…”
Section: Epigenetic Regulation Of Adipose Developmentmentioning
confidence: 99%
“…ING1b is the most widely expressed isoform of ING1, while ING2a is the major isoform of ING2. Their tumor suppressor functions have been concerned with many biological processes including gene transcription, cell growth control, apoptosis, and cellular senescence [10,11]. Their role as tumor suppressors is supported by the fact that their expression is decreased or lost in many human tumors [12].…”
Section: Introductionmentioning
confidence: 99%